2020
DOI: 10.1182/bloodadvances.2020001482
|View full text |Cite
|
Sign up to set email alerts
|

Venetoclax and hypomethylating agents (HMAs) induce high response rates in MDS, including patients after HMA therapy failure

Abstract: Key Points Treatment-naive and relapsed/refractory MDS patients receiving venetoclax and HMAs have an ORR of 59% with 63% of responders proceeding to transplant. Allogeneic stem cell transplantation after treatment with venetoclax in combination with HMA is associated with prolonged survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
77
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(86 citation statements)
references
References 14 publications
7
77
0
Order By: Relevance
“…A recent multi-institutional retrospective analysis of forty-four treatment naïve or relapsed MDS patients (IPSS-R very high risk (41%), poor or very poor-risk cytogenetics (43%), therapy-related MDS (34%), prior treatment with HMA (73%), and >10% marrow blasts (57%)) treated with a combination of venetoclax with either azacitidine or decitabine, yielded an overall response rate of 59% with two-thirds of patients successfully bridged to AHSCT 41 . Response breakdown was as follows: 14% CR, 27% mCR with hematologic improvement, and 18% mCR without hematological improvement.…”
Section: Venetoclax In Mds and Other Chronic Myeloid Malignanciesmentioning
confidence: 99%
“…A recent multi-institutional retrospective analysis of forty-four treatment naïve or relapsed MDS patients (IPSS-R very high risk (41%), poor or very poor-risk cytogenetics (43%), therapy-related MDS (34%), prior treatment with HMA (73%), and >10% marrow blasts (57%)) treated with a combination of venetoclax with either azacitidine or decitabine, yielded an overall response rate of 59% with two-thirds of patients successfully bridged to AHSCT 41 . Response breakdown was as follows: 14% CR, 27% mCR with hematologic improvement, and 18% mCR without hematological improvement.…”
Section: Venetoclax In Mds and Other Chronic Myeloid Malignanciesmentioning
confidence: 99%
“…Guadecitabine is a dinucleotide of decitabine and deoxyguanosine linked by a phosphodiester bond, which is gradually cleaved, leading to a slow-release and thus prolonged cellular exposure of its active metabolite decitabine [ 122 , 123 ]. The most promising combinatorial strategies include a combination with the selective BCL-2 inhibitor, venetoclax [ 124 ] and the mutant p53 reactivator, APR-246 [ 125 , 126 ]. The combination with venetoclax and azacitidine has been FDA-approved for the treatment of AML in adults of 75 years or older (21 November 2018, , accessed on 6 April 2021), while the combination with APR-246 has received the breakthrough designation in MDS patients with TP53 mutation (1 April 2020, , accessed on 6 April 2021).…”
Section: Epigenetic Drugsmentioning
confidence: 99%
“…Clinical trials with APR-246 in combination with azacitidine are ongoing and have shown high response rates in high-risk MDS patients, albeit only in those with the deactivating p53 mutation [ 126 ]. Venetoclax in combination with azacitidine increased response and prolonged survival compared to azacitidine treatment alone in MDS patients [ 124 ]. Overall, hypomethylating agents still represent the best treatment strategy for many high-risk MDS patients [ 127 ], and combinatorial treatment schemes hold the promise to improve response and to reduce the onset of primary and secondary resistances.…”
Section: Epigenetic Drugsmentioning
confidence: 99%
“…The BCL2-inhibitor, venetoclax, in combination with HMAs or LD-AraC, has shown substantial activity and has advanced to the standard of care in first-line treatment of elderly patients with AML [145]. This combination has showed promising efficacy also in MDS and is currently further investigated in the first-line and HMA relapsed/refractory settings [146][147][148]. Nevertheless, the management of hematological toxicity remains a major challenge and requires careful monitoring of patients, dose adaptations and supportive treatment with growth-factors, antibiotics, and antimycotics.…”
Section: Higher-risk Mdsmentioning
confidence: 99%